Secretory IgA specific for herpes simplex virus in lacrimal fluid from patients with herpes keratitis--a possible diagnostic parameter. Issue 10 (October 1982) - Pedersen, B; Møller Andersen, S; Klauber, A; Ottovay, E; Prause, J U; Zhong, C U; Norrild, B
Abstract : In the present study a solid-phase radioimmune assay was used for the demonstration of herpes simplex virus-specific IgG and secretory IgA antibodies in the lacrimal fluid from patients with active recurrent herpes keratitis. The method was quantitative and made it possible to test specifically for the production of secretory IgA antibodies produced during an active herpes simplex virus infection. The production of secretory IgA was followed in 2 patients with fresh recurrent lesions. The HSV-specific secretory IgA could be demonstrated during the first 10 days of infection, where the maximal concentration was reached 3-5 days after the first symptoms occurred. The secretory antibodies were locally produced, and it is shown for the first time that herpes virus-specific secretory antibodies were of diagnostic value.